1998
DOI: 10.1002/(sici)1096-8628(19980630)78:2<155::aid-ajmg11>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Low blood folates in NTD pregnancies are only partly explained by thermolabile 5,10-methylenetetrahydrofolate reductase: Low folate status alone may be the critical factor

Abstract: Thermolabile 5,10-methylenetetrahydrofolate reductase (MTHFR) is the first folate-related variant to be associated with an increased risk of neural tube defects (NTDs). The variant causes high plasma homocysteine levels and reduced red cell folate (RCF) levels, both of which have also been linked to an increased risk of NTDs. We examined the relationship between folate status and presence of the common mutation MTHFR C677T in 82 NTD-affected and 260 control mothers. Homozygosity for the TT genotype was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 21 publications
(39 reference statements)
1
35
0
Order By: Relevance
“…Two previous reports establishing that homocysteine and folate status of the mother has an impact on NTD outcome have highlighted the need to verify whether the maternal genotype has a direct effect on NTD risk. 39,40 In fact, it is plausible that maternal genotype could play a particular pathogenic role in NTDs, either by limiting the supply of folate to the embryo or by facilitating the accumulation and increased transfer to the embryo of homocysteine, high concentrations of which can disrupt neural tube closure in experimental models. Unfortunately, owing to sparse data, we are unable to estimate potential NTD risk among mothers carrying four mutations in genes involved in folate-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous reports establishing that homocysteine and folate status of the mother has an impact on NTD outcome have highlighted the need to verify whether the maternal genotype has a direct effect on NTD risk. 39,40 In fact, it is plausible that maternal genotype could play a particular pathogenic role in NTDs, either by limiting the supply of folate to the embryo or by facilitating the accumulation and increased transfer to the embryo of homocysteine, high concentrations of which can disrupt neural tube closure in experimental models. Unfortunately, owing to sparse data, we are unable to estimate potential NTD risk among mothers carrying four mutations in genes involved in folate-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The thermolabile MTHFR 677C fi T (A222V) variant is a risk factor for neural tube defects (NTDs) in some but not all populations (Botto and Yang 2000) and is associated with low folate and elevated homocysteine levels. However, the MTHFR 677TT genotype accounts for only 11.4% of the population attributable fraction in Ireland (Shields et al 1999) and only partly explains low blood folates in NTD pregnancies (Molloy et al 1998). This has led to the search for additional polymorphisms which influence folate and/or homocysteine levels in relation to neural tube defects, cardiovascular disease and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that low vitamin B12 concentrations could lead to reduced methylation of homocysteine to methionine, enhancing the impairment of folate metabolism and increasing the risk for development of NTDs (van der Put and Blom, 2000). It has also been reported that the combination of MTHFR polymorphisms and low folate and vitamin B12 intake is associated with a greater risk for NTDs than each variable alone, indicating a strong genetic-nutritional interaction (Molloy et al, 1998;Stegmann et al, 1999). Cunha et al (2002) reported that the mutant C allele was not associated with differences in folate and vitamin B12 concentrations in children with NTDs.…”
Section: Discussionmentioning
confidence: 99%